Catecholamine Vasopressors and the Risk of Atrial Fibrillation After Noncardiac Surgery: A Prospective Observational Study - Li W; Liu Y; Gu X (Dove Medical Press, 2024)
Weichao Li,1,2 YuYan Liu,2 Xunhu Gu1 1Department of Neurology, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People's Republic of China; 2Department of Anesthesiology, Affiliated Qingyuan Hospital (Qingyuan People's Hospital), Guangzhou Medical University, QingYuan, Guangdong, People's Republic of ChinaCorrespondence: Xunhu Gu, Doctor of Medicine (MD), Department of Neurology, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, 330006, People's Republic of China, Email 540523118@qq.comBackground: Catecholamine vasopressors are commonly used for intra- or post-operative hypotension for cardiac surgery, which have a side effect of new-onset atrial fibrillation (AF) and myocardial ischemia. However, it is not entirely clear whether catecholamine vasopressors increase the risk of new-onset AF after noncardiac surgery.Aim: The aim of this study was to analyze the association between the use of catecholamine vasopressors and the risk of developing new-onset AF after noncardiac surgery.Methods: In this prospective trial, available data from eligible elderly individuals receiving noncardiac surgery at a single center from November 2022 to January 2024 were gathered. Propensity score matching (PSM) was used to balance patient baseline characteristics and to control for confounders. To determine the association between catecholamine vasopressors and the risk of new-onset AF, univariate and multivariate logistic regression analyses were performed.Results: A total of 6000 subjects were included in this study (mean [SD] age, 70.73 [6.37] years; 910 [50.9%] males). After PSM, the patients were stratified into catecholamine vasopressor (n = 357) and comparator groups (n = 1432). A total of 18/357 patients in the catecholamine vasopressor group developed AF, and 25/1432 patients in the comparator group developed AF (incidence rate, 5.0% vs 1.7%). Compared with the comparator group, the catecholamine vasopressor group had an increased risk of new-onset AF (aOR, 2.77; 95% CI, 1.28- 5.89). Some sensitivity analyses also revealed consistent findings of increased new-onset AF risk associated with catecholamine vasopressor treatment.Conclusion: The findings from this study suggest that catecholamine vasopressor treatment is associated with an increased risk of new-onset AF and may help physicians select a modest medication for patients while also assessing the risk of new-onset AF. Keywords: catecholamine vasopressors, new-onset atrial fibrillation, risk, prospective trial, noncardiac procedures